PREVISÃO DE DEMANDA URBANA DE ÁGUA: UMA ANÁLISE DO CONSUMO DE ÁGUA EM ESTABELECIMENTOS COMERCIAIS NO DISTRITO FEDERAL - Totugui, Natália; Valverde, Bruna; Sant'ana, Daniel (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Federal District faces water stress since 2016, with alarming low levels of water availability for urban water supply. In order to reduce urban water demand and promote water conservation, it is crucial to understand how water is being used by different types of buildings. This article aims to classify the different commercial activities to identify commercial water consumption indicators in commercial units in the District Federal, and with that, elaborate an urban demand forecast model. The methodology was based on the composition of a representative model that consists of a quantitative survey, number of samples, characterization of the typology (population, areas, activities developed, etc.) and water demand for the creation of a land consumption indicators (l/p/d, l/m²/d, etc.). The indicators creation are important to design building systems and monitoring the evolution of consumption in commercial activities. It was found, as a result, that the best variable of consumption corresponds the total of population in commercial activities. In addition, analyses of correlation and regression showed that all independent variables affect water demand.